MATH-Domain Family Shows Response toward Abiotic Stress in Arabidopsis and Rice - Kushwaha, Hemant R.; Joshi, Rohit; Pareek, Ashwani; Singla-Pareek, Sneh L. (Frontiers in Plant Science, 2016)
Response to stress represents a highly complex mechanism in plants involving a plethora of genes and gene families. It has been established that plants use some common set of genes and gene families for both biotic and abiotic stress responses leading to cross-talk phenomena. One such family, Meprin And TRAF Homology (MATH) domain containing protein (MDCP), has been known to be involved in biotic stress response. In this study, we present genome-wide identification of various members of MDCP family from both Arabidopsis and rice. A large number of members identified in Arabidopsis and rice show the expansion and diversification of family in both the species. Localization of MDCP genes on the chromosomes of both Arabidopsis and rice show their presence in a few specific clusters on various chromosomes such as chromosome III in Arabidopsis and chromosome X in rice. For the functional analysis of MDCP genes, we used publicly available data for plant growth and development as well as biotic stresses and found differential expression of various members of the family. Further, we narrowed down 11 potential candidate genes in rice which showed high expression in various tissues and development stages as well biotic stress conditions. The expression analysis of these 11 genes in rice using qRT-PCR under drought and salinity stress identified OsM4 and OsMB11 to be highly expressed in both the stress conditions. Taken together, these data indicate that OsM4 and OsMB11 can be used as the potential candidates for generating stress resilient crops.